Unit 9.45 Measurement of Autophagy by Flow Cytometry. Issue 1 (1st April 2014) - Warnes, Gary
Abstract: In recent years, flow cytometry has been used to detect the presence of autophagy mainly by the fluorescent antibody labeling of the autophagy marker, the microtubule associated protein LC3‐II. Here we describe the indirect antibody labeling of LC3‐II in cells displaying drug‐induced autophagy by the use of rapamycin and chloroquine, as well as cells undergoing serum starvation. Although the mechanism of action of LysoTracker dyes is not fully understood, lysosomal mass increases during the autophagic process to enable the cell to produce autolysosomes. Given that LC3‐II and LysoTracker are measuring different biological events in the autophagic process, they surprisingly both up‐regulated during autophagic process. This approach shows that although LysoTracker dyes do not specifically label lysosomes or autophagosomes within the cell, they allow the simultaneous measurement of an autophagy related process and other live cell functions, which is not possible with the standard LC3‐II antibody technique. Curr. Protoc. Cytom . 68:9.45.1‐9.45.10. © 2014 by John Wiley & Sons, Inc.